2008
DOI: 10.1212/01.wnl.0000303813.95800.0d
|View full text |Cite
|
Sign up to set email alerts
|

Rufinamide for generalized seizures associated with Lennox–Gastaut syndrome

Abstract: Rufinamide was an effective and well-tolerated treatment for seizures associated with Lennox-Gastaut syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
372
4
39

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(425 citation statements)
references
References 53 publications
10
372
4
39
Order By: Relevance
“…Key inclusion criteria for this study were as follows: (a) children and adults ages 2 to 54 years with onset of LGS before [18][19][20] that included patients with characteristics similar to those of patients in the CONTAIN trial (i.e., age range, number of drop seizures, seizures not controlled by previous regimens, use of study drug therapy as adjunctive therapy). Felbamate was excluded, as none of its studies were conducted with patients of characteristics similar to those in the clobazam, rufinamide, topiramate, and lamotrigine trials.…”
mentioning
confidence: 99%
“…Key inclusion criteria for this study were as follows: (a) children and adults ages 2 to 54 years with onset of LGS before [18][19][20] that included patients with characteristics similar to those of patients in the CONTAIN trial (i.e., age range, number of drop seizures, seizures not controlled by previous regimens, use of study drug therapy as adjunctive therapy). Felbamate was excluded, as none of its studies were conducted with patients of characteristics similar to those in the clobazam, rufinamide, topiramate, and lamotrigine trials.…”
mentioning
confidence: 99%
“…Glauser et al (2008) принимали участие 138 пациентов с СЛГ в возрасте от 4 до 30 лет. Критерии включения предполагали ча-стоту приступов не менее 90 в месяц до начала терапии руфинамидом.…”
Section: детской неврологииunclassified
“…Получены достоверные различия по частоте дроп-атак, тониче-ских / атонических приступов (p < 0,0001) в группе ру-финамида (средняя редукция частоты -42,5 %) по сравнению с группой плацебо (увеличение часто-ты -1,4 %). В группе руфинамида отмечено значи-тельное уменьшение тяжести приступов (p = 0,0041) и более высокая доля респондеров (уменьшение ча-стоты приступов на 50 % и более) как в отношении частоты всех приступов (p = 0,0045), так и дроп-атак (p = 0,002) [8].…”
Section: детской неврологииunclassified
“…15 Patients were between the ages of 4 and 30 years, were treated with 1 to 3 AEDs at baseline, and had at least 90 seizures in the month before study entry. Three end points that were addressed were the percent change in total seizure frequency for 28 days, the percent change in atonic seizure frequency in 28 days, and seizure severity based on apparent parent/guardian global evaluation.…”
Section: Efficacymentioning
confidence: 99%
“…More unique to rufinamide is the potential for cardiac conduction disturbances with QT interval shortening. 14,15 In the placebo-controlled trial, the observed degree of QT shortening was mild; nevertheless, the potential for increased risk of ventricular arrhythmia should be noted. Rufinamide should be avoided in patients with familial short QT syndrome and used with caution in combination with other drugs that shorten QT interval.…”
Section: Adverse Effectsmentioning
confidence: 99%